Multi-Group Analysis for Purchase Intention Based on Gender: Can Perceived Value Always Mediate Consumer Trust? - Religia, Yoga; Ambarwati, Sri Dwi Ari; Pamuji, Windy Anindya (AIBPM Publisher, 2023)
This study investigates the factors influencing consumer purchase intentions in the informal small retail sector in developing countries. Although informal retail businesses play an important role in emerging economies, research on consumer purchase intentions at small retailers is limited. In this study, we used secondary data from 281 respondents and conducted a multi-group analysis based on gender using SmartPLS. The results showed that consumer trust did not have a significant influence on purchase intention, while perceived value turned out to have a significant positive influence on purchase intention. In addition, the perceived value can act as a full mediation between consumer trust in purchase intention. Multi-group analysis revealed gender differences in the influence of perceived value on purchase intention. The practical implication of the study is that small retailers need to consider the importance of creating value for consumers in their marketing strategies, as well as understand how gender differences can affect consumer purchase intention.